Association between systemic immunity-inflammation index and sex hormones in children and adolescents aged 6–19 - Gao, Zijun; Liu, Ke (Frontiers in Endocrinology, 2024)
Objectives: This study aimed to evaluate the relationship between systemic immune-inflammation index (SII) and sex hormones in children and adolescents aged 6-19 years. Methods: Data were obtained from the National Health and Nutrition Examination Survey (NHANES) conducted between 2013 and 2016. Inclusion criteria comprised subjects aged 6-19 years with complete data on both SII and sex hormones. We employed weighted multiple regression analysis and subgroup analytical methods to independently estimate the relationship between SII and sex hormones. Results: In this study, a total of 3767 participants were included, with an average age of 12.32 ± 3.95 years. Males constituted 50.54%, and females 49.46%. Among males, a statistically significant negative correlation emerged between SII and sex hormone-binding globulin (SHBG). Similarly, in the female population, SII exhibited a statistically significant negative correlation with total testosterone (TT), SHBG, and the Ratio of TT to estradiol, while maintaining a positive correlation with free androgen index (FAI). Subgroup analysis underscored variances in the association between sex hormones and SII within cohorts distinguished by pubertal status or different body mass index (BMI). In addition, the relationship between SII and estradiol exhibited nonlinearity. Employing a two-segment linear regression model, we identified an inverted U-shaped association between SII and estradiol, with an inflection point of 748.09 (1000cell/ml). Conclusion: Our findings suggest that SII may be an independent risk factor for changes in sex hormones in both male and female children and adolescents. More prospective and experimental studies should be conducted to validate our results and elucidate the underlying molecular pathways.